Comparison of data warehousing and big data principles from an economic and technical standpoint and their applicability to natural gas remote readout systems - Kluk, Vedran (Array, 2019)
In natural gas remote reading, a large amount of data is collected, posing a problem of storing and processing such data to the companies involved. Two major technologies have recently appeared, becoming a de facto standard in processing large amounts of data, i.e., data warehousing and big data. Each of these technologies provides different data processing techniques. In this paper, serial data processing and parallel data processing are considered in data warehousing and big data, respectively. The paper analyzes the feasibility of implementing new technologies for processing a large amount of data generated by remote reading of natural gas consumption. The research conducted in this paper was made in collaboration with a local natural gas distribution company. A comparison of potential software vendors has shown that Qlik offers the best software package for the requirements provided by the local natural gas distribution company. Comparison results have also shown that other potential vendors also offer software packages of good quality.